Paving Pathways for Educational Technology Talent: Connecting Fresh Graduates to Industry Opportunities in Indonesia - Rengga Prakoso Nugroho; Mochammad Hilman Amirudin Nahri; Jundu Muhammad Mufakkirul Islami; Tantra Nur Syamsiah; Zahra Zain Rifandini (Proceeding of the International Conference on Global Education and Learning, 2024)
The National Educational Technology Talent Survey (NETTS) addresses the gap between Educational Technology graduates and private sector job opportunities in Indonesia. By connecting students, alumni, and industry practitioners, NETTS fosters professional readiness and promotes the recognition of Educational Technology in diverse fields. Using a research and development framework, NETTS developed activities including job market surveys, webinars, and training workshops to enhance graduate competencies. Findings indicate a lack of awareness among students regarding industry roles, despite existing market demand. Positive feedback from alumni and participants highlights NETTS’ potential to create a sustainable ecosystem for collaboration and knowledge exchange. Future initiatives should focus on expanding partnerships with industry stakeholders and student associations to maximize program impact.